2014
DOI: 10.3389/fmicb.2014.00594
|View full text |Cite
|
Sign up to set email alerts
|

Microbial sulfur transformations in sediments from Subglacial Lake Whillans

Abstract: Diverse microbial assemblages inhabit subglacial aquatic environments. While few of these environments have been sampled, data reveal that subglacial organisms gain energy for growth from reduced minerals containing nitrogen, iron, and sulfur. Here we investigate the role of microbially mediated sulfur transformations in sediments from Subglacial Lake Whillans (SLW), Antarctica, by examining key genes involved in dissimilatory sulfur oxidation and reduction. The presence of sulfur transformation genes througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 134 publications
(163 reference statements)
2
55
0
Order By: Relevance
“…Similar sequences are found in other environmental samples including lake sediments [81,82] and in Blood Falls [8] but the organisms containing them have not been isolated or characterized. Below 8 cm, key genes involved in sulfate reduction were observed [52]. The appearance of dissimilatory sulfite reductase (dsrA) and aprA related to known sulfate-reducing prokaryotes within the genera Desulfobacterium and Desulfotomaculum indicate the potential for sulfate reduction [52].…”
Section: (D) a Chemosynthetic Ecosystem Below Icementioning
confidence: 99%
See 4 more Smart Citations
“…Similar sequences are found in other environmental samples including lake sediments [81,82] and in Blood Falls [8] but the organisms containing them have not been isolated or characterized. Below 8 cm, key genes involved in sulfate reduction were observed [52]. The appearance of dissimilatory sulfite reductase (dsrA) and aprA related to known sulfate-reducing prokaryotes within the genera Desulfobacterium and Desulfotomaculum indicate the potential for sulfate reduction [52].…”
Section: (D) a Chemosynthetic Ecosystem Below Icementioning
confidence: 99%
“…The water column of SLW was more species rich than the surficial sediments (0-2 cm depth) containing 3931 and 2424 groups or OTUs. Cluster analysis indicated that the top 2 cm of sediments and water column were similar [7] but community structure at sediment depths below 2 cm were statistically different ( [52]; A Achberger 2015, unpublished data). The Betaproteobacteria were the most abundant bacterial division in both the water (more than 38% of sequences) and sediments (more than 59% of sequences).…”
Section: (D) a Chemosynthetic Ecosystem Below Icementioning
confidence: 99%
See 3 more Smart Citations